ANALISIS CEMARAN LOGAM (Ca, Cu, Mg dan Si) DALAM ABU TERBANG PABRIK SEMEN - Meyci Trisna; Edi Kurniawan; Nina Hartati (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2023)
Fly ash is produced in the combustion process of coal in a factory. It can be used in the construction industry, particularly in cement and concrete production. Moreover, fly ash has been added as one of the materials in cement production due to composition similarities between fly ash and other raw materials. However, fly ash is not environmentally friendly as it contains inorganic compounds that are harmful to the environment. Therefore, it is important to know its properties and characterization for further research, advantages and disadvantages that follows. This study was focusing on the Ca, Cu, Mg and Si in fly ash as a byproduct of coal combustion. Based on the results, SiO2 and CaO levels consecutively are 21,17% and 0,65% indicated that fly ash can be added as one of the materials used in cement production. Furthermore, the toxic Cu and Mg in fly ash displayed its safety in the environment, in sequence are 0,02855ppm and 0,81825ppm.